HIV status disclosure among adults attending care and treatment clinic in Kilombero district, South-Eastern Tanzania - Mazuyi Emmanuel John; Beatrice Chipwaza (Elsevier, 2022)
Background: Disclosing HIV serostatus is important for HIV prevention and in reducing HIV transmission among communities. The present study assessed HIV disclosure patterns and its associated factors among adults in Kilombero district, Tanzania. Methods: A cross-sectional study was conducted among people living with HIV who visited Care and Treatment Clinic in Ifakara Town Council from September 2018-February 2019. A structured questionnaire was used to collect data, and the analysis was done by SPSS Version 20. Results: A total of 102 participated into this study, 63 (61.8%) females and 39 (38.2%) males. The mean age (±SD) of participants was 34.37 (±10.9) years and people living with HIV were mostly (68%) in age group between 18 and 38. Despite the high rate of HIV disclosure 81 (79.4%) only 58% had disclosed their HIV results to their partners. In addition, most partcipants delayed the disclosure for six months and above. HIV disclosure was significantly higher in married participants than in single individuals (81.8% vs 68.5%; p < 0.001), and in participants aged 39-59 years (p = 0.06). The major reasons for non-disclosure include fear of losing their partners, felt ashamed of being HIV positive and fears of stigma. Conclusion: Although the disclosure of HIV serostatus among the participants was high, the disclosure to their sex partners was moderate. Moreover, the study observed negative attitudes and delayed disclosure longer than six months. Interventions to promote disclosure of HIV and discouraging stigma and discriminations should be given priority.